The Phenomenon of Patting Sakinah and Its Relationship with Pre-Marriage: a Psychological and Ethical Review of Islam - Rouf, Abdur; Hidayat, Riyadhul; Rifaldi, Yoga; Railana, Ipan (Yapilin Press, 2025)
The phenomenon of Tepuk Sakinah is a form of religious and cultural expression that develops among the young generation of Indonesian Muslims, especially in pre-marriage activities, sakinah family training, and community-based da'wah programs. This study aims to analyze the symbolic meaning and psychological function of Tepuk Sakinah in forming marriage readiness, as well as examining its conformity with Islamic adab and ethical values. The approach used is library research with qualitative-descriptive analysis, accompanied by a critical analysis of the theory of Social Learning (Bandura), Experiential Learning (Kolb), and the concept of manners in classical and contemporary Islamic ethics. The results of the study show that Tepuk Sakinah is not just a means of entertainment, but functions as a medium for internalizing Islamic moral values through symbolic and affective learning mechanisms. Psychologically, this practice fosters emotional readiness, self-control, and moral awareness which play an important role in the formation of marriage readiness. Meanwhile, in terms of Islamic ethics, Tepuk Sakinah reflects the principle of performative adab, namely the application of spiritual values in the form of communicative and meaningful social actions. This study confirms that the integration between local culture and Islamic values can be an effective strategy in moral- and character-based pre-marriage education. This research has implications for the development of a Cultural Islamic Moral Pedagogy model that can be applied in pre-marriage guidance programs, adolescent da'wah, and culture-based character education. These findings also reinforce the idea that the learning of Islamic values can be packaged creatively, contextually, and humanistically without losing its theological substance.